DESIGN AND BUILD OF A SMALL FIXED WING UAV FOR SEARCH AND RESCUE APPLICATION - SYEED, FARHAN; HASNAYEEN, ASIF; IQBAL, MD. REDWAN; SHEIKH, MORSALIN (My University, 2024)
The entire design and development process of a small fixed-wing Unmanned Aerial Vehicle (UAV) made especially for Search and Rescue (SAR) missions is presented in this thesis. Because of its adaptability, agility, and capacity to reach difficult or isolated areas, unmanned aerial vehicle (UAV) technology has become a potentially useful instrument for improving search and rescue (SAR) operations in recent years. Nevertheless, the specialized elements required for successful SAR flights are frequently absent from current commercial UAVs such as telemetry, radio transmitters etc. The primary objective of this research is to bridge this gap by designing and building a custom UAV optimized for SAR applications. The design process involves a systematic approach encompassing aerodynamic analysis, structural design, payload integration. Furthermore, the integration of sensors, including GPS and cameras, enables the UAV to effectively detect and locate individuals or objects in challenging terrain and environmental conditions. To ensure that the planned UAV prototype performs well and is reliable for real-world applications, it is put through testing and assessment in our MIST field.
DESIGN AND BUILD OF A SMALL FIXED WING UAV FOR SEARCH AND RESCUE APPLICATION